Revisiting size effect due to work of new surface formation in mechanical micro-machining using FEM - Srinivas Rao U.; Vijayaraghavan L. (My University, 2025)
Finite element simulations of chip formation have been carried out for uncut chip thickness of 4 μm to 24 μm by incorporating Johnson-Cook fracture model to study the energy spent in new surface formation in metal cutting. The plastic dissipation and the damage dissipation energy of the chip formation are analyzed for the orthogonal machining simulations carried out. From the analysis it has been shown that the damage dissipation energy in machining is negligible compared to the plastic dissipation energy and it increases with the enhancement in the ratio of uncut chip thickness to edge radius of the cutting tool. © 2017 Elsevier Ltd.